The supreme agent strategy for efficient searching and manifesting vital cloud services - S, Dhanasekaran; V, Vasudevan (International Journal of Engineering and Technology, 2018)
The supreme agent technique deals with devise and magnification of software agents for effectively discovery appropriate cloud services, cloud service agreement and cloud service assortment. This research work establishing an agent based strategy for composing variety of relevant cloud services and provides unified virtualized service to the cloud customers in a effective manner. The contribution of research work includes developing cloud service search engine for efficient cloud service discovery, and dealing both provider and consumer by means of supreme agent strategy. This supreme agent scheme uses an enhanced fuzzy based ranking algorithm. This supreme agent system works on behalf of cloud user and provider to list out various cloud providers with necessary information to enable the user to choose relevant cloud service in a reasonable time period. Cloud agreement mechanism facilitates the agreement activities among client agent & intermediate agent also among intermediate agent & supplier agent. Cloud service assortment facilitate the agent vigorously choose the Cloud services and records the display the available cloud services.